Bee Venom Effect on Glioblastoma Cells Viability and Gelatinase Secretion - Małek, Agata; Kocot, Joanna; Mitrowska, Kamila; Posyniak, Andrzej; Kurzepa, Jacek (Frontiers in Neuroscience, 2022)
Background: The involvement of MMP-2 and MMP-9 in the pathogenesis of various kinds of cancers including glioblastoma is well documented. The evaluation of the anticancer potential of honey bee (Apis mellifera) venom (BV) consisting of the inhibition of MMP-2 and MMP-9 secretion in a glioblastoma cell culture model was the aim of the study. Methods: 8-MG-BA and GAMG human primary glioblastoma cell lines vs HT-22 mouse hippocampal neuronal cells were applied for the study. The BV dose (0.5, 1.0, 1.25, 1.5, 1.75, 2.0, 2.5, and 5.0 µg/ml) and time-dependent (24, 48, 72h) cytotoxicity was evaluated with the tetrazolium-based colorimetric assay (MTT test). MMP-2 and MMP-9 activities in the cell culture medium under different BV concentrations were determined by gelatin zymography. Results: A dose and time-dependent BV effect on cytotoxicity of both glioblastoma cell lines and hippocampus line was observed. The weakest, but statistically important effect was exerted by BV on HT-22 cells. The greatest cytotoxic effect of BV was observed on the 8-MG-BA line, where a statistically significant reduction in viability was observed at the lowest BV dose and the shortest incubation time. The reduction of both gelatinases secretion was observed at 8-MG-BA and GAMG lines without significant effect of HT-22 cell line. Conclusions: In vitro studies indicate that BV has both cytotoxic and inhibitory effects on the secretion of MMP-2 and MMP-9 in selected lines of glioma, suggesting anticancer properties of BV.